1988
DOI: 10.2105/ajph.78.12.1563
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of lower extremity stress fractures: a controlled trial of a shock absorbent insole.

Abstract: A prospective controlled trial was carried out to determine the usefulness of a viscoelastic polymer insole in prevention of stress fractures and stress reactions of the lower extremities. The subjects were 3,025 US Marine recruits who were followed for 12 weeks of training at Parris Island, South Carolina. Polymer and standard mesh insoles were systematically distributed in boots that were issued to members of odd and even numbered platoons. The most important finding was that an elastic polymer insole with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
130
1
6

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(149 citation statements)
references
References 24 publications
12
130
1
6
Order By: Relevance
“…15,42 There is general support for progressive forms of training-a gradual buildup in the frequency, duration, and intensity of exercise, especially early in training. 8,12,41,43 We suggest that a consistent alternateday running schedule, with 2 days of rest from both marching and running, be included each week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,42 There is general support for progressive forms of training-a gradual buildup in the frequency, duration, and intensity of exercise, especially early in training. 8,12,41,43 We suggest that a consistent alternateday running schedule, with 2 days of rest from both marching and running, be included each week.…”
Section: Discussionmentioning
confidence: 99%
“…Overuse injuries of the lower extremities are common in the military and have been associated with the rigors of marching, drilling, and running. 1,[11][12][13][14][15] These studies have found that 3% to 6% of male Army recruits get stress fx/rx during their 8-week basic training, and 10% to 20% have overuse injuries in general. This rate of overuse injury adversely affects military training, resulting in lost training days and increased medical costs.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations that have examined polyurethane and sorbothane insoles worn in the boots of Marine or Amiy recmits have shown no effect on stress fractures, lower extremity musculosketal injury rates, or sick call rates during military training (16,80,170). However, a study that examined a polyurethane orthotic insole worn in the boots of Israeli basic trainees found a reduction in femoral stress fractures but no influence on tibial or metatarsal stress fractures; when the incidence of all types of stress fractures was combined, there was a significant reduction in incidence among the insole users (180).…”
Section: (2) Equipment Modification Strategiesmentioning
confidence: 99%
“…High plantar pressures have been linked to foot pain and discomfort (Gardner et al, 1988;Godfrey et al, 1967;Hodge et al, 1999;Silvino et al, 1980). Many researchers have performed studies to compare the effectiveness of reducing plantar pressure with different materials (Leber and Evanski, 1986) and shoe inserts (Chiu and Wang, 2007;Lee and Hong, 2005;Tsung et al, 2004).…”
mentioning
confidence: 99%